2012
DOI: 10.4111/kju.2012.53.9.632
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Emergency Ureteroscopic Management of Ureteral Calculi

Abstract: PurposeTo evaluate the efficacy and safety of the ureteroscopic management of ureteral stones immediately after a first colic attack.Materials and MethodsWe retrospectively analyzed the data of 226 patients with obstructive ureteral stones who underwent ureteroscopy with stone retrieval. The 67 patients in group A underwent ureteroscopy within 48 hours of admission to our emergency department, whereas the 159 patients in group B underwent ureteroscopy more than 48 hours after admission. The chi-square test was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
4
13
0
1
Order By: Relevance
“…They observed that greater stonefree rate was achieved in patients with stones < 10 mm (95.8% versus 89%; p = 0.002) and in those presenting with stones in distal ureter (94.6 versus 71.4%; p = 0.004). The role of stone location and size as key factors in determining the success of URS was also confirmed by Youn et al who found a higher stone-free rate when only distal ureteral stones were considered (97.6 versus 89.8%), and fewer complications when only stones <10 mm were taken into consideration (2.7 versus 7.96%) [16]. Picozzi et al estimated that every 1 mm of increased diameter over 8 mm determine a reduction of stone-free rate of 5% in distal ureter and 8.1% in proximal ureters [11].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…They observed that greater stonefree rate was achieved in patients with stones < 10 mm (95.8% versus 89%; p = 0.002) and in those presenting with stones in distal ureter (94.6 versus 71.4%; p = 0.004). The role of stone location and size as key factors in determining the success of URS was also confirmed by Youn et al who found a higher stone-free rate when only distal ureteral stones were considered (97.6 versus 89.8%), and fewer complications when only stones <10 mm were taken into consideration (2.7 versus 7.96%) [16]. Picozzi et al estimated that every 1 mm of increased diameter over 8 mm determine a reduction of stone-free rate of 5% in distal ureter and 8.1% in proximal ureters [11].…”
Section: Discussionmentioning
confidence: 70%
“…The definition of emergency varied among the studies from 12 to 48 h from admission to the emergency room. Stone-free status was defined on postoperative imaging (KUB in 3 studies and CT scan in one), which was done at 1 month in most studies (Table 1) [16][17][18][19]. In six studies (4 prospective randomized controlled and 2 retrospective case-control studies), emergent ESWL (n = 356) was compared to delayed ESWL (n = 355).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Emergency URS reduces the need for medications (analgesics, anti-inflammatory) and prolonged hospitalization. This is achieved at a lower cost, 27 with comparable success and safety. Emergency URS is recommended, on the other hand, at the expense of discontinuing conservative (medical) treatment, admission, anesthesia and abandoning the expectant approach for spontaneous stone passage.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the following factors: failure after a trial of medical expulsion therapy (MET) would lead to the clinical decision for emergency ureteroscopy; the median waiting time for emergency surgery was 26h; and most patients would stay an additional day post-surgery for symptom monitoring before they are discharged. In contrast, EL is performed as Day Surgery procedures [4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%